Building a city by building schools: school festivals in Nova Iguaçu (1916-1947) - Amália Dias (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This article presents the results of doctoral research in which the social function of the school was investigated with regard to the ways in which educational institutions mobilize and participate in the public scene of the city. The analysis of ceremonies and festivals held by schools or in which they participated, based on the local press and notes in school attendance charts, reveals a productive area that represents the intertwining between school and city and the school's function with regard to the organization of spaces and people. These events, particularly school festivals and public celebrations, point to the construction of a role of the school for instruction not only in aspects of literacy but also in behavioral habits, moral values, and rights of citizenship. The investigation focused on Nova Iguaçu, a city in the state of Rio de Janeiro. In addition to examining the interplay between city and school, the following were also considered relevant: the collaborative process in which school and city are mutually constructed and how educational practices exercised in schools by students and teachers can also be educational for the city's population, thereby establishing schooling as a way of socializing.